Analisis Perbandingan Metode SMART dan MOORA Dalam Penentuan Pelanggan Terbaik - Very Hendra Saputra; Nuroji (CV. Keranjang Teknologi Media, 2024)
Determining the best customers is a critical process in customer management where companies seek to identify and assess customers who contribute most significantly to business success. The problem that occurs in determining the best customer is that there is no method used in determining the best customer, so far only based on the number of purchases from customers without any other aspects that are decisive. This study aims to apply and compare the determination of the best customers using the SMART and MOORA methods so as to provide better insight to decision makers about the choice of method that best suits the characteristics and complexity of the decision at hand. The ranking results show that the best customers are obtained by Sulistia with rank 1 either using the SMART method or the MOORA method. A comparison of ranking results between the SMART and MOORA methods can provide useful insight into the extent to which both methods are effective in addressing multi-criteria decision making. Based on the results of the ranking comparison between the SMART and MOORA methods, there are differences in rankings in 2 data, namely on behalf of Handoko with the SMART method getting rank 3 and with the MOORA method getting rank 2, and on behalf of Subagio with the SMART method getting rank 2 and with the MOORA method getting rank 3. The results of the comparison between the SMART and MOORA methods in determining the best customers recommend the MOORA method compared to the SMART method, because the results of the conformity level of the MOORA method get a value of 99.996% higher than the SMART method which gets a value of 99.995%.